(untitled) (American Journal of Islam and Society, 1985)
Translation In the name of Allah, most benevolent, ever-merciful. 19. Truly man was created Very impatient; 20. Fretful when evil Touches him; Good reaches him; 22. Not so those decoted To prayer; 23. Those who remain steadfast To their prayer; 24. And those in whose wealth Is a recognised right; 25. For the (needy) who asks And him who is prevented (For some reason from asking); 26. And those who hold To the truth of the Day Of Judgment; 27. And those who fear The displeasure of their Lord, . . . 29. And those who guard Their chasity, . . . ; 32. And those who respect Their trusts and covenants; 33. And those who stand firm In their testimonies; 34. And those who guard (The sacredness) of their worship; 35. Such will be The honoured ones In the Gardens (of Bliss). Surah LXX. For behavioral scientists, especially psychologists and psychiatrists, most of whom these days are preoccupied with wide-spread psychological anxieties and suicidal behavior, the Qur’an in this part of Surah al Ma’arij proposes certain traits and qualities of man which counter human fears and anxieties. It is the duty of Muslim behavioral scientists in general and psychiatrists in particular to study and research these Qur’anic directions and propositions about human nature, and the traits, habits and behaviors necessary to counter their negative effects on human life, peace and mind and gratification. It is their duty to make people understand the important role of these Qur’anic directions in human life and suggest the ways and means to the Muslims to develop ...